2020
DOI: 10.22159/ijcpr.2020v12i6.40303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myopia on Primary Open Angle Glaucoma

Abstract: Objective: It is a retrospective study to evaluate the effect of myopia on primary open-angle glaucoma by classifying the eyes into NMG (non-myopic glaucoma), HMG (highly myopic glaucoma) And MMG (mild to moderate myopic glaucoma). Methods: The study was performed on 120 patients with primary open-angle glaucoma who were medically treated. Any participant who had surgery done was excluded from the study. The relation between glaucoma and different myopia and progression were assessed on the basis of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The findings are in agreement with previous studies. [10][11][12] It has been suggested that myopia may increase the intraocular pressure (IOP), causing glaucomatous damage. The association between myopia and POAG was suggested decades ago by Loyo-Berrios et al 13 The previous study review showed that IOP is one of the major risk factors for POAG, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are in agreement with previous studies. [10][11][12] It has been suggested that myopia may increase the intraocular pressure (IOP), causing glaucomatous damage. The association between myopia and POAG was suggested decades ago by Loyo-Berrios et al 13 The previous study review showed that IOP is one of the major risk factors for POAG, among others.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Kimura et al, 23 reported that highly myopic and non-highly myopic eyes show a difference in the progression of glaucoma changes. Reddy et al, 10 evaluated the effect of myopia on POAG by dividing the 120 patients into three categories; those with non-myopic glaucoma (NMG) and highly myopic glaucoma (HMG) and mild-moderate myopic glaucoma (HMG) respectively. They reported mixed results of no glaucoma progression in 14 myopes and progression of glaucoma in 5 myopes.…”
Section: Discussionmentioning
confidence: 99%